1974
DOI: 10.1021/jf60195a025
|View full text |Cite
|
Sign up to set email alerts
|

California bay oil. II. Biological effects of constituents

Abstract: AGFD-44. Reference to a company or product name does not imply approval or recommendation of the product by the U. S. Department of Agriculture to the exclusion of others that may be suitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…Similarly, Müller‐Riebau et al found that L. nobilis oil only showed a slight effect against Fusarium moniliforme and Phytophthora capsici , and even had no effect against Rhizoctonia solani and Sclerotinia sclerotiorum at 1000 µL mL −1 . In these reports, the main components of L. nobilis oil were reported as 1,8‐cineole, sabinene, α ‐pinene, linalool, α ‐terpinyl acetate and β ‐pinene, which were the important components for inhibiting the growth of pathogens . However, in our study, we found that the main components of our tested essential oil were quite different, with the conjecture that the production area and the environment influenced the components of the essential oil.…”
Section: Discussioncontrasting
confidence: 61%
“…Similarly, Müller‐Riebau et al found that L. nobilis oil only showed a slight effect against Fusarium moniliforme and Phytophthora capsici , and even had no effect against Rhizoctonia solani and Sclerotinia sclerotiorum at 1000 µL mL −1 . In these reports, the main components of L. nobilis oil were reported as 1,8‐cineole, sabinene, α ‐pinene, linalool, α ‐terpinyl acetate and β ‐pinene, which were the important components for inhibiting the growth of pathogens . However, in our study, we found that the main components of our tested essential oil were quite different, with the conjecture that the production area and the environment influenced the components of the essential oil.…”
Section: Discussioncontrasting
confidence: 61%
“…The biocidal activity of this plant has been associated with its high content in umbellulone (39%), which has been shown to be toxic when fed to laboratory mice. 11 Therefore, the high content of umbellulone in aerial parts of P. bahiana might be responsible for its reputed effectiveness to kill fleas.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the odor, flavor, and chemical compositions of these leaves are distinguishably different from the true bay leaf. The essential oils of the Californian bay leaf contain a volatile monoterpene, umbellulone, as a major component present solely in this plant species [12]. This toxic compound can cause a severe headache, sinus irritation, sneezing, and even unconsciousness in some sensitive individuals [13].…”
Section: Application Of Gc/q-tof Combined With Advanced Data Mining Amentioning
confidence: 99%